Changes in serum neurofilament light chain levels following narrowband ultraviolet B phototherapy in clinically isolated syndrome. Issue 2 (27th January 2022) - Fabis‐Pedrini, Marzena J.; Kuhle, Jens; Roberts, Katherine M. A.; Trend, Stephanie; Jones, Anderson P.; Maceski, Aleksandra; Carroll, William M.; Lucas, Robyn M.; Mastaglia, Frank L.; Hart, Prue H.; Kermode, Allan G.
Abstract: Objective: To determine whether serum neurofilament light chain (sNfL) levels are suppressed in patients with the clinically isolated syndrome (CIS) following narrowband ultraviolet B phototherapy (UVB‐PT). Methods: sNfL levels were measured using a sensitive single‐molecule array assay at baseline and up to 12 months in 17 patients with CIS, 10 of whom received UVB‐PT, and were compared with healthy control (HC) and early relapsing remitting multiple sclerosis (RRMS) group. sNfL levels were correlated with magnetic resonance imaging total lesion volume (LV) determined using icobrain version 4.4.1 and with clinical outcomes. Results: Baseline median sNfL levels were significantly higher in the CIS (20.6 pg/mL, interquartile range [IQR] 13.7–161.4) and RRMS groups (36.6 pg/ml [IQR] 16.2–212.2) than in HC (10.7 pg/ml [IQR] 4.9–21.5) ( p  = .012 and p  = .0002, respectively), and were strongly correlated with T2 and T1 LV at 12 months ( r  = .800; p  = .014 and r  = .833; p  = .008, respectively) in the CIS group. Analysis of changes in sNfL levels over time in the CIS group showed a significant cumulative suppressive effect of UVB‐PT in the first 3 months (UVB‐PT −10.6% vs non‐UVB‐PT +58.3%; p  = .04) following which the levels in the two groups converged and continued to fall. Conclusions: Our findings provide the basis for further studies to determine the utility of sNfL levels as a marker of neuro‐axonal damage in CIS and early MS and for assessing the efficacy of new therapeutic interventions such as UVB‐PT. Abstract : Serum neurofilament light chain (sNfL) levels were measured using a sensitive single‐molecule array assay at baseline and up to 12 months in 17 patients with the clinically isolated syndrome (CIS), 10 of whom received UVB‐phototherapy and seven did not receive UVB‐phototherapy. Longitudinal comparisons of sNfL levels in the UVB‐phototherapy treated versus non‐UVB‐phototherapy CIS participants using a mixed‐effects model showed that over the first 3 months there was a significant cumulative suppressive effect of UVB‐phototherapy.